The virtue of participatory governance: a MacIntyrean alternative to shareholder maximization. (August 2015) - Bernacchio, Caleb; Couch, Robert
Abstract : We draw on Alasdair MacIntyre's virtues, practices, and institutions schema to argue that employee participation in governance practices can play an important role in developing virtue. Whereas MacIntyre's schema has been most widely employed to understand how productive practices can cultivate virtue, we focus instead on the way that meaningful deliberation about the common good can provide experiences requiring employees to exercise the virtues. We then apply this theoretical framework to an analysis of the Mondragon Cooperative Corporation. Our analysis emphasizes the importance of participatory governance over employee ownership. Based on this analysis, we draw several implications for increasing participatory governance in a way that will prevent shareholder maximization from crowding out virtue, even in corporate contexts where productive activity itself does not provide a meaningful, virtue‐instilling experience.